3D bio-etching of a complex composite-like embryonic tissue1. Issue 16 (21st August 2015) - Hazar, Melis; Kim, Yong Tae; Song, Jiho; LeDuc, Philip R.; Davidson, Lance A.; Messner, William C.
<x xml:space="preserve">Abstract</x> To investigate the collective movements within 3D multilayered tissues our group has focused on developing a novel microfluidic technique capable of creating complex patterns in multicellular structures.